PERBEDAAN KADAR HEMOGLOBIN SEBELUM DAN SESUDAH DONOR DARAH DENGAN PEMERIKSAAN METODE POCT (Point of Care Testing): Hemoglobin, Blood Donation, POCT Method - Rosidah; Retno Twistiandayani; Indah Vauzyana; Edy Agustian Yazid (Jurnal Penelitian Multidisiplin, 2022)
Hemoglobin is a metalloprotein, which is an iron-containing protein in red blood cells that functions as a carrier of oxygen from the lungs throughout the body. Blood donation is the process of transferring blood or blood elements from one person to the circulatory system of another. The purpose of this study was to determine the difference in hemoglobin levels before and after blood donation by examining the POCT (Point of Care Testing) method. The characteristics analyzed were hemoglobin levels before and after blood donation. The results of this study showed that the average hemoglobin level before blood donation was 14,654 gr/dl and the average hemoglobin level after blood donation was 14,289 gr/dl. From the results of data analysis using the SPSS program, the results obtained are sig (2-tailed) 0.002. Because sig (2-tailed) < , 0.002 <0.05, H0 is rejected and H1 is accepted. Thus, the results obtained are that there are differences in hemoglobin levels before and after blood donation using the POCT (Point of Care Testing) method. The difference in the amount of hemoglobin in the donor is caused by several factors, such as gender, age, weight, and others.